PENGARUH AKSES INFORMASI DETEKSI DINI KANKER CERVIX TERHADAP PEMERIKSAAN INSPEKULO VISUAL ASAM ASETAT PADA WANITA USIA SUBUR DI WILAYAH PUSKESMAS GADING KABUPATEN PROBOLINGGO - Hidayati, Tutik; Iis Hanifah (Jurnal Medicare, 2025)
A preliminary study regarding access to information on early detection of cervical cancer in Gading Village, obtained data that out of 30 WUSs there were 21 people who stated that they had never received information about the importance of early detection of cervical cancer and had never undergone an IVA examination. This study aims to determine the relationship between access to information on early detection of cervical cancer and inspecular visual examination of acetic acid (IVA) in women of childbearing age. This study used an observational research design through a cross sectional approach. This research was conducted in the area of Puskesmas Gading, Lumajang Regency. The sample size was 92 people with the simple random sampling technique. The results showed that 65 people (70.7%) of WUS had received information about early detection of cervical cancer. Inspecular visual examination of acetic acid on WUS showed that most of the 48 people (70.7%) had not undergone IVA examination. The relationship between access to information on early detection of cervical cancer and inspection of the Inspecular Visual Acetic Acid (IVA) at WUS in Gading Village with a p value of 0.000 with a contingency coefficient of 0.525 is classified as a strong relationship. Conclusion WUS in Pandan Arum Village has received information about early detection of cervical cancer. Most of the women of childbearing age in the village of Gading have not yet undergone an IVA inspection of the Inspekulo Visual acetic acid. There is a significant relationship between access to information on early detection of cervical cancer with inspection of the Inspecular Visual Acetic Acid (IVA) in Women of Fertile Age (WUS) in Gading Village, the Working Area of Puskesmas Gading. Suggestions for further research, in order to do a joint study between quantitative and qualitative studies (Mix Method) so that more comprehensive information can be obtained.